A study on the clinical value of prophylactic contralateral central lymph node dissection in patients with cT1-T2N1b unilateral papillary thyroid cancer - Suqiong Lin; Rongliang Qiu; Yujuan Tang; Xiaoquan Hong; Qiangbin Ding; Ke Li; Ende Lin; Penghao Kuang; Jinbo Fu; Jinbo Fu; Guoyang Wu (Frontiers in Oncology, 2025)
BackgroundsLateral lymph node metastasis (cN1b) is a major factor affecting the prognosis and recurrence of papillary thyroid cancer (PTC). Currently, there is some controversy regarding whether to dissect the contralateral central lymph nodes in patients with cT1-T2N1b unilateral PTC. The purpose of this study was to investigate the risk factors for contralateral central lymph node metastasis (CCLNM) and to summarize the significance of prophylactic contralateral central lymph node dissection (CCLND), to provide reference information for clinical intervention.MethodsThe data of 99 patients with cT1-T2N1b unilateral PTC from August 2021 to October 2024 were retrospectively analyzed. Multifactorial analysis was performed using logistic regression to analyze the risk factors for CCLNM in patients with cT1-T2N1b unilateral PTC. The analysis of the CCLNM rate and metastasis mode summarized the clinical significance of prophylactic CCLND.ResultsCCLNM occurred in 55 cases (55/99,55.6%), and the total number of lymph nodes cleared from the contralateral central lymph node was 6.1 ± 4.9, of which the number of metastatic lymph nodes was 1.5 ± 1.9; There was no statistically significant difference between the CCLNM and non-metastasis groups in terms of the rate of lymph node metastasis in the ipsilateral lateral cervical region (zones II, III, IV and V) and the ipsilateral central zone (P>0.05). There was no statistically significant difference between the metastatic group and the non-metastatic group in terms of the number of lymph nodes cleared in the ipsilateral lateral cervical region (zones II, III, IV and V) (P > 0.05). Compared with the non-metastatic group, the metastatic group had more positive lymph nodes and fewer negative lymph nodes in the ipsilateral central region, and the difference was statistically significant (P < 0.05). Logistic regression analysis showed that microcalcification and Hashimoto’s thyroiditis in the metastasis group were independent factors for the occurrence of CCLNM, and the difference was statistically significant (P<0.05).ConclusionThe occurrence of CCLNM in cT1-T2N1b unilateral PTC is related to several factors. Lymph node dissection can help reduce the risk of recurrence and reoperation due to CCLNM; therefore CCLND cannot be ignored.